If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 6(x + 7) Reorder the terms: -9 + 6x = 6(x + 7) Reorder the terms: -9 + 6x = 6(7 + x) -9 + 6x = (7 * 6 + x * 6) -9 + 6x = (42 + 6x) Add '-6x' to each side of the equation. -9 + 6x + -6x = 42 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + 0 = 42 + 6x + -6x -9 = 42 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 = 42 + 0 -9 = 42 Solving -9 = 42 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6/b-1=9/1 | | 6x+36/35x+20/3x+18/7x+4 | | 2(x+3)=8(x-2)-2 | | N-13+6=8 | | -16-5n=(-6+8n)+3 | | 3x-5+2=20 | | -9+12x=75 | | -25+7x-4x=53 | | (4p^-5/p^5)^3 | | x-6=4x+3 | | 4y+17=3y-26 | | 10b-5b=55 | | 6+2p-2=8p+14-4p | | 5x-18=63 | | x/-5=17 | | 7m-77-16m-60=28 | | 2-5y=14 | | 8(t-4)+7t=(3t-3)-12 | | 9+7x=-68 | | 7(h+3)=2(6m+8) | | 1/4x-2/3y=8 | | 10x-(9x-6)=10 | | 1/9*9w | | 3(4z+2)-7=95 | | 4x+3/12+x-3/2=3x+1/4 | | 3/4(2x-6)=1/2x-4 | | 3(5h-12)=9 | | 0=3x^2+4 | | 0=3x^2-900 | | 52=28-3(x-4) | | a-2b=8 | | 12.95x=388.5 |